Analisis Faktor Penentu Keputusan Pembelian Konsumen pada Industri Fast Food: Peran E-WOM, Harga, dan Citra Rasa pada Almaz Chicken - Rini Martiwi; Instianti Elyana; Nyoman Suardhita; Aan Rahman; Aloysius Rangga Aditya Nalendra (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), price, and taste perception on consumer purchase decisions at Almaz Chicken, as well as to explain the phenomenon of business performance decline marked by the closure of several outlets. This research employs a quantitative approach using explanatory research design. Data were collected through questionnaires distributed to 150 respondents selected using simple random sampling. data analysis was conducted using multiple linear regression with SPSS. The results show that partially, E-WOM, price, and taste perception have a positive and significant effect on purchase decisions. Taste Perception is Identified as the most dominant variable influencing consumer decisions. Simultaneously, all independent variables significantly affect purchase decisions, with an F-Value of 48.672 and a significance level of 0.000. The coefficient of determination (R Square) is 0.589, indicating that 58.9% of the variation in purchase decisions can be explained by the model. These findings suggest that in the culinary industry, consumption experience reflected through taste perception plays a crucial role in sustaining purchase decisions, while E-WOM and price act as supporting factors. The decline in Almaz Chicken’s performance is likely driven by inconsistencies in product quality, which trigger negative E-WOM and reduce perceived value among consumers. Therefore, maintaining consistent product quality is essential for business sustainability.